0
$\begingroup$

Prove p, assuming the following:

  • (1) r → ¬q assumption
  • (2) q assumption
  • (3) ¬(p ∧ ¬s) ∧ (¬r → p) assumption
  • I need help after (4) not sure how to start this

  • (4) q → ¬r contrapostion (1)

  • (5)¬r modus ponens (2),(4)

  • (6)

  • (7)

$\endgroup$
2
  • $\begingroup$ (4) is wrong.... $\endgroup$ Commented Jan 24, 2019 at 16:45
  • $\begingroup$ Use Contraposition on (1) to get $q \to \lnot r$. Then use MP with (2) to get $\lnot r$. $\endgroup$ Commented Jan 24, 2019 at 16:46

1 Answer 1

0
$\begingroup$

Prove p, assuming the following:

(1) r → ¬q assumption (2) q assumption (3) ¬(p ∧ ¬s) ∧ (¬r → p) assumption I need help after (4) not sure how to start this (4) q → ¬r contrapostion (1) (5)¬r modus ponens (2),(4) (6) p Modus ponens (3),(4) I figured it out!

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .